Nilai-Nilai Pendidikan K.H. Hasyim Asy'ari dan Relevansinya dalam Pembentukan Karakter Profil Pelajar Pancasila pada Siswa Sekolah Dasar - Witasari, Rinesti; Siregar, Maragustam (IBTIDA', 2025)
One of the Muslim intellectuals in Indonesia who is very influential in the field of education, especially in forming a personality with character, is K.H Hasyim Asy'ari. The purpose of this research is to explore the educational values of K.H. Hasyim Asy'ari and its relevance in the formation of the character of Pancasila Students in elementary school students. This study uses a qualitative approach to library research. This method was chosen to explore and comprehensively understand the concept of character education as taught and practiced by K.H. Hasyim Asy'ari, a very influential Islamic education figure in Indonesia and how it is relevant to the Formation of Pancasila Student Profile Character in elementary school students. This study found that K.H. Hasyim Asy'ari's educational values, such as honesty, piety, mutual cooperation, and independence, are said to be relevant in the formation of the character of Pancasila Students in elementary school students. The integration of basic values in the curriculum shows an increase in positive behaviors, such as tolerance, cooperation, and responsibility. The integration of K.H. Hasyim Asy'ari's values shows the importance of incorporating local wisdom in the character education curriculum, which can strengthen students' cultural identity. Primary schools need to integrate K.H. Hasyim Asy'ari's educational values into the curriculum systematically, ensuring that these values are taught in every subject.